A Descriptive Study of the Implementation Regulations of The Governor of Yogyakarta Special Region No. 68 the Year 2012 in Kindergarten Mlati Sub Regency of Sleman - Shabrina, Monita Nur; Latiana, Lita (BELIA: Early Childhood Education Papers, 2018)
As a social creature and comes from a country that has a cultural diversity, Indonesia is expected to have community education based on the culture. But in an era of modernization is increasingly reduced public awareness about the importance of cultural education. Yogyakarta is one of the local culture is still strong and the local government is also very concerned with the education of culture in this Government made official rules about culture-based education that is Regulation The Governor of the Yogyakarta Region stimewa No. 6 Year 2012 about guidelines application of sublime cultural values in the management and organization of education. The purpose of this research is to know the process of learning and teachers ' perception about Javanese culture-based learning as the imlementasi rule gubenur Daerah Istimewa Yogyakarta. Research methods used in this type of qualitative research is the subject of research is the KINDERGARTEN educators in Mlati, Sleman. Pengupulan engineering researchdata on the menguunakan observation, interviews, and documentation, while data analysis through the process of data collection, data presentation, data reduction, and verification of data as well as the withdrawal of the conclusion. The results of this research mennjukan that all learning in kindergarten subdistrict already integrated with Javanese culture in accordance with the official rules of the Government, and educators know only as the core of the regulation only, not knowing in depth , because of the lack of socialization from the Government but the kindergarten teacher in Mlati is so supported the Government by having such a regulation because it promoted good for continuity of learning.